(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the evidence available in the scientific literature on the role of nurses in sensitizing the family of potential donors of organs and tissues. Methodology: This is an Integrative Literature Review, exploratory with a qualitative approach on the role of nurses in sensitizing the family of potential organ donors, carried out in the national and international databases, in the period from 2015 to 2020. It used the acronym PICO is used to construct the research question and perform the bibliographic search. Result: 5 articles were selected, 4 of which are nursing publications, while 1 is a multidisciplinary publication involving different areas of health. From the results found, three thematic categories were formed: The moment of news: communicate the family about death; The moment of the interview and Skills and personal and professional characteristics needed by the interviewer. Conclusion: The theme of organ and tissue donation is still permeated by taboos and ignorance on the part of those who experience the death of a family member with potential for donation. The research made it possible to learn nursing care for the Potential Donor in a broader dimension, from care for donor patients and support for family members, to management activities between intra-hospital commissions and organ procurement organizations.